Artificial intelligence for language learning and teaching: A narrative literature study (Englisia : Journal of Language, Education, and Humanities, 2024)
The purpose of this study was to examine teachers' beliefs, the factors that influence the use of AI tools, and the advantages, disadvantages, opportunities, and threats of artificial intelligence in language learning and teaching. To accomplish this, the study used a narrative literature review and ATLAS.ti 9 to analyze the data. The results of the study showed that teachers believed that Artificial Intelligence in Language Learning and Teaching (AILLT) included assessing student needs, developing appropriate learning resources, promoting collaboration among resources, providing real-time assessment tools to improve the educational process, and increasing teaching efficiency and effectiveness. Second, AI tools for writing tools, including Paperpal, Quillbot, Jenni AI, ChatGPT, Elicit, as well as in applications to improve speaking skills, such as Speeko and Vocaroo, and "Siri and Say It" for listening and pronunciation skills. Third, factors that may influence students' use of AI-based language learning tools include adaptability, engagement, motivation, autonomy, immediate or direct feedback, accessibility and inclusivity, and teacher and parent support. This research found that AI enhances accessibility, adaptability, personalization, and immediate feedback, but it also has limitations, such as dependence on technology, inadequate human interaction, limited contextual understanding, and algorithmic biases. In addition, AILLT faces potential threats such as quality control, privacy concerns, and job or task displacement. Narrative literature studies provide theoretical insights, and it is expected that future studies at different levels of language learning will incorporate empirical evidence from experimental and case study-based research.
Keywords: Artificial intelligence; Chatbot; Language learning; Instant feedback; Quillbot